Electrolytic double-spraying sample preparation method for analyzing second phase in nickel-based superalloy
By using electrolyte with 15-25% concentrated sulfuric acid and 75-85% methanol for electrochemical corrosion, the problem of easy falling off of the second phase particles of nickel-based high-temperature alloy is solved, and the clear profile of the second phase particles and the retention of complete carbide particles is achieved, and the accuracy of the analysis is improved.
Patent Information
- Application Number
- CN202411651076.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art In the TEM electrolytic double spray sample method for preparing nickel-based high-temperature alloys, the second phase particles are prone to fall off, resulting in misjudgment of analysis, and there are limitations in the corrosion liquid and process.
Electrolyte with 15-25% concentrated sulfuric acid and 75-85% methanol is used to conduct electrochemical corrosion by electrolytic double spraying method, and the working voltage is controlled to be 15-20V and the working temperature is between -20--10°C, so as to achieve passivation protection of the matrix phase, corrosion and dissolution of the γ′ phase, and avoid the fall of carbides and the like.
A clear second-phase particle profile and complete carbide particles were obtained, avoiding analysis misjudgment, and improving sample cleanliness and analysis accuracy.
Smart Images

Figure CN119574241A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal physical chemistry, and in particular relates to an electrolytic double-spraying sample preparation method for analyzing a second phase (γ′ phase, carbide, oxide phase, etc.) in a nickel-based high-temperature alloy. Background Art
[0002] Nickel-based high-temperature alloys have excellent strength and high-temperature performance, good oxidation resistance and heat corrosion resistance, high organizational stability and reliability, and are used in key components of aerospace engines. In addition to the matrix, it also contains second phases such as γ′ phase and various carbide phases. Due to the small size of the second phase (usually below a few hundred nanometers), high-precision scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are usually used for quantitative analysis. In order to accurately perform quantitative analysis and evaluate the influence of the analyzed phase on the material properties, the analyzed phase is required to be as clear as possible, with clear boundaries, no omissions, and no interfering elements introduced during the corrosion process. Therefore, strict requirements are placed on the composition and preparation process of the etching solution for microstructural characterization samples.
[0003] γ′ phase (Ni 3 (Al, Ti) phase) is the main strengthening phase of nickel-based superalloys. The distribution and size of the γ′ phase are important factors affecting the performance of the alloy. The γ′ phase in nickel-based superalloys is often small in size and densely distributed. The more accurate the statistical quantification is. Due to the limitations of the preparation process, the carbide phase is an inevitable second phase in nickel-based superalloys. There are many carbide phases in nickel-based superalloys, such as MC, M 3 C.M. 6 C.M. 7 C 3 、M 23 C 6 etc. Most types of carbides are incompatible with the matrix or γ′ phase, have high strength but high brittleness, and are considered to be harmful to performance and cannot be completely avoided. The only way is to strictly control the heat treatment process, crush them during processing, and strictly limit their size and content. In addition, the MC carbide phase formed at the boundary of the original powder particles will become the nucleation site of the γ′ phase, which will cause the formation of coarse γ′ phase and weaken the precipitation strengthening effect. However, it is also found that M 23 C 6 The phase and the γ′ phase have a coherent interface, and proper size control can be used to improve material properties. With the further improvement of the high-temperature performance and service performance requirements of nickel-based high-temperature alloys, the study of carbide phases is becoming more and more important. Not only limited to its shape distribution, but also its formation mechanism, phase structure, interface state, element segregation, etc. also need further analysis, which puts higher requirements on TEM characterization and sample preparation. In the TEM electrolytic double-spray sample preparation method for γ′ phase and carbide of nickel-based high-temperature alloys, the existing etching solutions and processes have their own limitations.
[0004] For example, the patent number ZL202210595866.6 uses 180 mL of concentrated H 3 PO 4 Solution, 6 mL concentrated H 2 SO 4 Solution and 8g CrO 3 The electrolyte can better expose the γ′ phase, but there are problems such as too fast corrosion of the matrix and the shedding of carbide particles, which causes phase loss and is not conducive to analysis. 3 It is highly toxic and will introduce Cr elements into the matrix, which is not conducive to elemental analysis. Patent No. ZL201310110911.5 uses a mixed solution of 10% perchloric acid + 90% anhydrous ethanol, which also has the problem of uncontrollable corrosion rate and carbide particles falling off. Patent No. ZL202410776559.7 uses an electrolytic corrosion solution with a volume ratio of 3 parts hydrochloric acid, 1 part nitric acid, 0.5-1 part propylene glycol, and 0.5-1 part phosphoric acid to observe the metallographic corrosion of dendrites, but is not conducive to the observation of precipitation phases. Patent No. ZL 201310110911.5 uses two kinds of etching solutions to prepare samples through electrochemical etching for metallographic structure observation of the second phase. The first method uses a mixed solution of 30-45% sulfuric acid and 55-70% methanol to remove the matrix phase, and the second method uses a mixed solution of 10-20% sulfuric acid, 5-15% hydrogen peroxide, and phosphoric acid as an etching solution to remove the γ′ phase to observe the carbide phase. The corrosion mechanism of this method is to remove the matrix phase, but there are problems such as the corrosion and dissolution of the matrix phase around the second phase, and the loss of the wrapped second phase falling off, resulting in analytical errors of carbides, oxide phases, and non-metallic inclusions, and the process is more cumbersome and complicated. It can only prepare metallographic structure samples, and cannot be used for TEM sample preparation. The corrosion process and results are relatively unstable. Summary of the invention
[0005] In order to solve the problem that the second phase particles of high temperature alloys are easy to fall off during the existing TEM sample preparation, resulting in misjudgment of analysis, the purpose of the present invention is to provide a sample preparation method for analyzing the second phase in nickel-based high temperature alloys. The method can obtain a clear second phase particle outline and complete carbide particles, and will not cause etching to carbides, etc., and at the same time solve the problem of misjudgment of analysis caused by the shedding of second phase particles during corrosion in the existing sample preparation method.
[0006] The technical solution adopted by the present invention is as follows:
[0007] An electrolytic double-spraying sample preparation method for analyzing the second phase in a nickel-based high-temperature alloy comprises the following steps:
[0008] (1) Pre-treating a nickel-based high-temperature alloy to obtain a sheet with a thickness of 50 to 100 μm;
[0009] (2) electrochemically corroding the thin slice obtained in step (1) by using an electrolytic double-spray method to achieve passivation protection of the matrix phase and corrode and dissolve the γ′ phase until a well-corroded SEM observation sample is obtained;
[0010] The conditions of the electrochemical corrosion are as follows: the working voltage is 15-20V; the working temperature is controlled between -20 and -10°C; and the electrolyte is 15-25% concentrated sulfuric acid and 75-85% methanol in terms of volume percentage.
[0011] Preferably, the electrolytic double-spray method in step (2) is to fix the thin slices in step (1) on the anode, place the cathode in the electrolytic cell, spray the electrolyte onto the thin slices through the electrolytic double-spray instrument, and electrolytically dissolve the thin slices through the external potential.
[0012] Preferably, the thin slice of step (1) is also double-sided polished; the etching time of step (2) is controlled as follows: first, the thin slice is corroded for 200±50s, taken out, washed with anhydrous ethanol and then observed; if the degree of corrosion is not enough, the thin slice is corroded again every 60±30s and observed.
[0013] After electrolysis, the samples were sequentially placed in three passes of anhydrous ethanol solution for cleaning and then blown dry.
[0014] Preferably, on the basis of the SEM observation sample, the electrochemical etching is continued in the same way until a suitable small hole appears in the middle of the sample to obtain the TEM observation sample. The TEM sample etching time control is determined by the photosensitive element of the electrolytic double-spray instrument receiving the infrared signal. When a perforation appears in the middle of the sample, the device will automatically stop working.
[0015] The above-mentioned SEM observation sample or TEM observation sample is used in analyzing the second phase in the nickel-based high-temperature alloy.
[0016] Preferably, the SEM observation sample or the TEM observation sample is used to analyze the γ′ phase, carbide, oxide phase and non-metallic inclusions.
[0017] Preferably, the SEM observation sample is placed under a scanning electron microscope, and the morphology, size and quantity of the γ′ phase are photographed and observed based on the γ′ phase imprint.
[0018] Preferably, the size and quantity of the γ′ phase are statistically analyzed by taking 20 photos at 3000-10000 times magnification and using image analysis software such as Image J to count the pixel areas on the photo plane.
[0019] An electrolytic double-spray sample preparation method for analyzing the second phase in a nickel-based high-temperature alloy, the specific steps are as follows:
[0020] S1. Sample pretreatment: After EDM wire cutting, hand grinding or mechanical thinning and double-sided polishing, punching with a punching machine The discs were cut and polished into disc samples with a thickness of 50 to 100 μm.
[0021] S2-1: Place the pre-treated wafer sample with a thickness of 50-100 μm in an electrolytic double-spray device for electrochemical thinning. The voltage is 15-20 V. The corrosion time is controlled as follows: first, corrode for 200 seconds, take out and wash with anhydrous ethanol, blow dry and observe. If the corrosion degree is not enough, corrode and observe again every 60 seconds.
[0022] S2-2: In step S4, the samples screened by SEM are selected for further thinning. The process parameters are the same as S2-1. The samples are thinned until a suitable small hole appears in the middle of the sample. As TEM observation samples, the wafer samples after electrolysis need to be cleaned three times in anhydrous ethanol.
[0023] S2-3: Liquid nitrogen is used for cooling during the electrolysis process, and the working temperature is controlled between -20 and -10°C to ensure a suitable sample corrosion rate, prevent the γ′ phase and carbide phase and other second phases from being eroded or falling off, and improve the surface flatness of the sample;
[0024] S2-4: Place the disc in anhydrous ethanol and continue cleaning it using an ultrasonic cleaner. Finally, use an ear cleaning bulb to blow dry the remaining ethanol on the surface and store it.
[0025] S3. Scanning electron microscope observation: After the samples were thinned and etched by S1-S2, the morphology, size and quantity of the γ′ phase can be observed under the scanning electron microscope according to the γ′ phase imprint. The statistical analysis of the size and quantity of the γ′ phase is completed by taking 20 photos at 3000-10000 times, and using image analysis software such as Image J to count the pixel area of the photo plane. After the observation is completed, the sample can be further thinned and perforated in the same way as a TEM observation sample.
[0026] The purpose of step S3 is: first, to use SEM to observe a wider field of view and observe the distribution of the γ′ phase in a larger range; second, it can be used as a preliminary screening of transmission samples to select other second phase samples that at least contain the target carbide phase.
[0027] S4. Electrolytic double-spray thinning and perforation: The wafers screened by S1-S3 are further thinned and perforated by electrolytic double-spray method. The process parameters are the same as S2. The corrosion time of TEM perforated samples is controlled by the photosensitive element of the electrolytic double-spray instrument after receiving the infrared signal. When a perforation appears in the middle of the sample, the equipment will automatically stop working.
[0028] S5. Transmission electron microscope observation: The disc samples that have passed S1-S4 can be further analyzed under a transmission electron microscope for carbides, etc. For example, the morphology of carbides can be observed at a higher magnification, and the crystal structure information of carbides below 100 nanometers can be analyzed through diffraction and high resolution.
[0029] Compared with the existing method of retaining the γ′ phase by corroding the matrix phase with an existing corrosive agent, when the matrix phase around the second phase corrodes and dissolves, the second phase that loses the wrapping will fall off, causing the problem of analytical errors caused by the falling off of carbides, oxide phases and non-metallic inclusions. Although there are a large number of γ′ phases in the alloy, the remaining ones are also the deeply embedded parts, and the boundary morphology is not very clear. The present invention selects 15-25% concentrated sulfuric acid and 75-85% methanol as double-spray electrolytes. During the electrolysis double-spray process, the passivation protection of the matrix phase is achieved by controlling the solution temperature and electrolysis parameters. The γ′ phase has a more negative corrosion potential, thereby corroding and dissolving. During the corrosion process, the γ′ phase dissolves and becomes smaller, while the matrix wrapping the γ′ phase will not be corroded, leaving a very clear imprint, obtaining more morphological detail information, and can be used for the morphology and size statistics of the γ′ phase. For carbides and oxide phases with more positive potential, no corrosion damage will occur, and the matrix phase around the second phase will not corrode and dissolve, and the second phase that loses its wrapping will fall off, causing the analysis error caused by the falling off of carbides, oxide phases and non-metallic inclusions, etc., to obtain a clear three-dimensional contour of the second phase particles and retain the phase interface with the matrix transition. In addition, by controlling the electrolytic double-spray parameters and time properly, the sample is thinned without perforation. At this time, the sample is in a corroded state and the surface is flat. Due to the thinning of the sample thickness, the contrast of different phases is enhanced, the resolution and imaging quality are improved, which is conducive to scanning electron microscopy observation. After the sample is observed under the scanning electron microscope, it can continue to be thinned and perforated as a transmission electron microscope sample. Since the sample is consistent with the preparation conditions, the continuity and consistency of the two can be guaranteed, and it has the advantages of both SEM and TEM observation.
[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0031] (1) The present invention provides an etchant that, in the process of electrolytic double-spraying sample preparation, controls the solution temperature and electrolytic parameters to corrode the γ′ phase and protect the matrix phase; after the γ′ phase is corroded and dropped, the surrounding matrix is protected, leaving a very clear γ′ phase imprint, from which information such as the γ′ phase morphology, size, and quantity distribution can be obtained. This is opposite to the mechanism of the existing etchant that corrodes the matrix phase and protects the γ′ phase, and has a complementary effect.
[0032] (2) The present invention can avoid the problem of carbide phase to be observed falling off and being lost due to corrosion of the wrapped matrix, and at the same time will not corrode the carbide phase and non-metallic inclusions, can clearly retain the outline of the second phase, and will not introduce impurity elements, which is conducive to elemental analysis and is suitable for the analysis and observation of second phases such as carbides in nickel-based high-temperature alloys.
[0033] (3) The present invention can be used not only to observe the γ′ phase and the carbide phase, but also to characterize the oxide phase formed during the alloy preparation process and the second phase such as non-metallic inclusions brought into the master alloy during smelting. Since these phases have a higher anodic potential than the γ′ phase, the interface between the phase and the matrix transition phase can be retained by controlling the electrolysis parameters and the corrosion rate.
[0034] (4) The present invention can be used for the preparation of SEM electrolytic corrosion samples and TEM samples at the same time. After the SEM electrolytic corrosion samples are observed, the electrolytic double-spray instrument is used to continue thinning and perforating according to the same process to obtain TEM samples. The two sample preparation conditions are the same, which can ensure the continuity and consistency of the two microscopic characterization methods, improve the efficiency and accuracy of microstructure characterization, and at the same time, the early SEM observation can also screen the best samples for TEM analysis.
[0035] (5) The present invention has the advantages of high sample preparation efficiency, high sample quality, and is suitable for the study of nanoscale second phases in nickel-based high-temperature alloys. The electrolytic double-spray etching solution used does not contain Cr ions and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The SEM images of the SEM samples prepared in Example 1 of the present invention at different magnifications;
[0037] Figure 2 Transmission electron microscope images of the TEM sample prepared in Example 1 of the present invention at different magnifications;
[0038] Figure 3 The nano-scale oxide distribution and morphology of the TEM sample at different magnifications in Example 1 of the present invention;
[0039] Figure 4 The carbide aggregation distribution mode and morphology of the TEM sample in Example 1 of the present invention.
[0040] Figure 5 This is the SEM image of the large-sized carbide phase and grain boundary phase shedding observed in Comparative Example 1.
[0041] Figure 6 This is the overall organizational morphology image taken by SEM in this ratio 1.
[0042] Figure 7a is an optical microscope photo of the thinned and perforated sample in Comparative Example 2. Figure 7 b is Figure 7 In the light-transmitted photo of a, we can see that in addition to the central hole, there are many small holes of different sizes. Figure 7 c is Figure 7 a SEM photo of the vicinity of the central hole. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0044] Example 1
[0045] This embodiment takes the FGH96 nickel-based high-temperature alloy sample as an example. According to the "China Aviation Materials Handbook", the main elements of the alloy sample are shown in the following table.
[0046] Table 1 Element composition of FGH96 nickel-based high-temperature alloy
[0047]
[0048] The specific steps are as follows:
[0049] (1) After taking a suitable position as a sample, use an electric spark wire cutting machine to cut out a 200-350 μm metal sheet as a pretreatment step, and then grind both sides of the sheet with 400#, 800#, 100#, 1200#, and 2000# diamond sandpaper in turn to reduce the thickness to less than 100 μm, and then polish both sides;
[0050] (2) The sample obtained in step (1) was placed in anhydrous ethanol and cleaned three times using an ultrasonic cleaner. The thin slice sample was punched into a The disc is polished with 2000# diamond sandpaper to remove the burrs around the disc;
[0051] (3) selecting 20% concentrated sulfuric acid and 80% methanol by volume to prepare the electrolyte;
[0052] (4) Electrolytic double-spray thinning is performed on the wafer sample after step (2), and the solution in step (3) is selected as the electrolyte. The voltage of the electrolytic double-spray instrument is 15 V. Liquid nitrogen is used for cooling during the operation, and the working temperature is controlled between -20 and -10°C. After electrolysis for about 300 seconds, the wafer sample is placed in anhydrous ethanol and cleaned three times with an ultrasonic cleaner; finally, the residual ethanol on the surface is blown dry with an ear cleaning bulb;
[0053] (5) Observe the sample using a scanning electron microscope. The acceleration voltage of the scanning electron microscope is preferably set to 3kV to -15kV. The backscattering mode is selected for the scanning electron microscope observation mode. Take 20 photos at 3000-10000 times magnification, and use image analysis software such as Image J to count the pixel area of the photo plane. After the observation is completed, the sample can be further thinned and perforated in the same way as a TEM observation sample;
[0054] (6) The disc sample screened in (5) is further thinned by electrolytic double spraying until the sample has suitable perforations. Finally, the sample is placed under a transmission electron microscope for observation to characterize the phase structure, element distribution and composition, and interface conditions of the nanoscale second phase and non-metallic inclusions.
[0055] Depend on Figure 1 It can be seen that the γ′ phase shedding leaves traces: the irregular pits near the grain boundary are traces of primary γ′ phase shedding, and the white particles in the pits are carbide phase / oxide phase; the smaller square and butterfly-shaped pits in the crystal are traces of secondary γ′ phase shedding; the dots below 100 nanometers are traces of primary γ′ phase shedding. It can be seen that the γ′ phase traces are very clear, with clear edges, and its shape, size, quantity and other information can be intuitively distinguished and counted. The nano-scale carbide / oxide phase is completely preserved, and its distribution, quantity and size information, phase structure, element distribution and other information can be clearly observed and analyzed. It is conducive to the study of carbide / oxide phases in alloys.
[0056] Depend on Figure 2 Secondary γ′ phase observed under TEM.
[0057] Depend on Figure 3 The observable nanoscale oxide phase has clear boundaries and well-preserved phase interfaces.
[0058] Depend on Figure 4 Carbide phases can be observed to be concentrated and distributed at the grain boundaries. These carbide phases are completely preserved, and the distribution characteristics, quantity, size information, etc. can be clearly observed. The phase interface is clear, and it can be found that the carbide phase is located inside the γ′ phase, which can serve as a site for the precipitation and growth of the γ′ phase.
[0059] Comparative Example 1
[0060] The difference between this embodiment and embodiment 1 is that: an electrolyte of 15% nitric acid and 85% alcohol is used for electrolytic double-spray corrosion, and the electrolytic conditions are a voltage of 12V and a temperature of -35°C.
[0061] Depend on Figure 5 , 6It can be seen that the grain boundary phase has fallen off seriously and the phase composition cannot be determined; the carbide phase has fallen off, and the small-sized carbide phase cannot be observed, and its phase structure and element composition cannot be determined. Only the deeply embedded large-sized carbide phase can be observed. The matrix corrosion degree is not enough, the density of the γ′ phase in the material is high, and the γ′ phase particles overlap with each other, which interferes with the contrast, making it difficult to distinguish details and not conducive to observation and statistics.
[0062] Comparative Example 2
[0063] The difference between this embodiment and embodiment 1 is that the voltage is 25V.
[0064] Depend on Figure 7 It can be seen that when the voltage is 25 V, the corrosion rate is too fast, dissolution and corrosion occur in some areas after the central hole is punctured, and there are multiple small holes in the thin area, which leads to light transmission and is not conducive to TEM observation.
[0065] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An electrolytic double-spraying sample preparation method for analyzing the second phase in a nickel-based high-temperature alloy, characterized in that: The steps include: (1) Pre-treating a nickel-based high-temperature alloy to obtain a sheet with a thickness of 50 to 100 μm; (2) electrochemically corroding the thin slice obtained in step (1) by using an electrolytic double-spray method to achieve passivation protection of the matrix phase and corrode and dissolve the γ′ phase until a well-corroded SEM observation sample is obtained; The conditions of the electrochemical corrosion are as follows: the working voltage is 15-20V; the working temperature is controlled between -20 and -10°C; and the electrolyte is 15-25% concentrated sulfuric acid and 75-85% methanol in terms of volume percentage.
2. The method according to claim 1, characterized in that The electrolytic double-spray method in step (2) is to fix the thin slices in step (1) on the anode, place the cathode in the electrolytic cell, spray the electrolyte onto the thin slices through the electrolytic double-spray instrument, and electrolytically dissolve the thin slices through the external potential.
3. The method according to claim 1, characterized in that The thin slice of step (1) is also double-sided polished; the etching time of step (2) is controlled as follows: first, the thin slice is corroded for 200±50s, taken out, cleaned with anhydrous ethanol and then observed; if the corrosion degree is not enough, the thin slice is corroded again every 60±30s and observed.
4. The method according to any one of claims 1 to 3, characterized in that: Based on the sample observed by SEM, electrochemical etching is continued in the same way until a suitable small hole appears in the middle of the sample to obtain a sample observed by TEM.
5. A SEM observation sample obtained by the method according to any one of claims 1 to 3.
6. A TEM observation sample prepared by the method according to claim 4.
7. Use of the SEM observation sample according to claim 5 or the TEM observation sample according to claim 6 in analyzing the second phase in a nickel-based high-temperature alloy.
8. The use according to claim 7, characterized in that: The SEM observation sample or the TEM observation sample is used to analyze the γ′ phase, carbide, oxide phase, and non-metallic inclusions.
9. The use according to claim 8, characterized in that: The SEM observation sample was placed under a scanning electron microscope, and according to the imprint of the γ′ phase, the morphology, size and quantity of the γ′ phase were observed and photographed.
10. The use according to claim 9, characterized in that: Statistical analysis of the size and quantity of the γ′ phase was performed by taking 20 photos at 3000-10000 times magnification and using image analysis software such as Image J to count the pixel area of the photo plane.
Citation Information
Patent Citations
Etchant for displaying metallographic structure of nickel-based high temperature alloy and method
CN103196733B
Electrolytic corrosion method of nickel-based powder superalloy
CN115090875A
Electrolytic corrosion agent for nickel-based superalloy dendritic structure analysis and application method
CN118653201A
Etchant for displaying metallographic structure of nickel-based high temperature alloy and method
CN103196733A
Method for preparing micron-order nickel-based high-temperature alloy powder transmission electron microscope film sample
CN107121316A
Cited By
Preparation method of interface transmission electron microscope sample of stainless steel-carbon steel composite plate
CN121298378A